The Role of AI in Enhancing Decision Making in Industrial Service Operations: A Systematic Literature Review - Ashiq, Kashif (My University, 2026)
This study focuses on the impact of Artificial Intelligence (AI) on industrial service operations with a particular focus on decision-making, operational efficiency, employee engagement, and digital transformation. Systematic Literature Review (SLR) was chosen as the research methodology that will be used to evaluate the existing literature on such topics as AI and management, as well as smart industrial operations. Literature search, screening, and the-matic analysis were applied to identify relevant publications. The research uses the latest insights from highly cited articles on methodologies and AI technologies to guarantee validity and theoretical relevance. The findings indicate that the use of AI improves the performance of industrial organizations through enhanced predictive modeling, automation, decision-making, and adaptability. It is also found that there are several barriers to the successful implementation of the technology in question, which include a lack of workforce support, ethical issues, employees' skills in using digital tools, and insufficient technology readiness. In addition, it is revealed that the digital transformation of organizations leads to sustainable development, an innovative at-mosphere, and competitiveness.
Keywords: decision making; artificial intelligence; digitalisation; industry; machine learning; optimisation; industrial automation; big data; automation; leadership (activity); fi=Johtaminen ja organisaatiot|en=Management and Organization|; Master’s Programme in Strategic Business Development